Hábitos de lectura durante la pandemia y post pandemia en el proceso de enseñanza-aprendizaje en los estudiantes del 6to año de educación general básica de la escuela de educación básica Miguel de Cervantes, en la ciudad del Baba, provincia los Ríos, periodo 2023- 2024 - Quintana Altamirano, Aracely Melisa (2023)
Reading habits are notions that guide the student to enhance his academic and intellectual development, therefore the present research work refers to Reading Habits During the Pandemic and Post Pandemic in the Teaching-ProcessLearning in the Students of the 6th year of General Basic Education of the Miguel de Cervantes Elementary School, in the City of Baba, Los Ríos Province, 2023-2024. The problem arises when witnessing low levels in the reading of the dicents. The objective coexisted in visualizing whether reading habits improve the teaching- learning process in students, plus three specific objectives that guided this research. Within the scientific framework, relevant information was captured by referencing the dependent and independent variable. This research uses a methodology of mixed approach, type of descriptive study with synthetic analytical methods, development of critical and interactive thinking, a sample of 106 students was obtained to whom the survey was applied and 4 teachers the interview. Once the data have been collected, it has been identified that the pandemic affected the knowledge of reading, for not practicing it during the pandemic, showing problems in school accompaniments that affect them presenting a poor reading. The research is consummated with the need to correct the negative aspects in the reading habits from the development of a proposal, entitled Guide of reading techniques to motivate students of Basic Education to acquire a reading habit in the teaching-learning processes.